Chronic Pelvic Pain and Associated Clinical Characteristics among Women in a Tertiary Care Center in Indonesia - Sumapradja, Kanadi; Chayadi, Thomas (Indonesian Socety of Obstetrics and Gynecology, 2017)
Objective: To determine the prevalence and various aspects associated with female chronic pelvic pain. Methods: During the period of January to March 2016, a crosssectional study was conducted at the Women’s Health Clinic of Dr. Cipto Mangunkusumo Hospital, Jakarta, Indonesia. Subjects were female who complained of pelvic pain for more than 6 months. We performed history taking, physical examination, and laboratory investigations including hs-CRP serum examination. We calculate the prevalence and describe the clinical characteristics and diagnosis of the patient. Quality of life and levels of hs-CRP were compared between the group of mild and severe pain. Results: In this study, the prevalence of CPP was 9.78%. We found 96.9% of gynecological disorders, 1% of urological disorders, and 2.1% of musculo-skeletal disorders. The most common diagnosis is endometriosis. The Clinical characteristics of patients were found 62.9% suffer for 6 months - 1 year with the intensity of pain (VAS) 7-10 as much as 51.5%. Levels of hs-CRP serum was around 1.99 (0.00 - 404, 53). We found a decreased in the quality of life of the patient. The physical domain score was 56 (38-81); the psychology domain score was 56 (31-100); the domain of social relationships was 59 (25-75); and the environmental domain score was 56 (31-94). Conclusion: Endometriosis is the most common diagnosis in female chronic pelvic pain of reproductive age. The pain causes a decreased in quality of life who suffer from it. [Indones J Obstet Gynecol 2017; 5-3: 154-159] Keywords: chronic pelvic pain, hs- CRP, intensity of pain, quality of life